Avaliação de concessões aeroportuárias através da teoria das opções reais: o caso do Aeroporto de Guarulhos - Nunes, Marcello Bastos (2015)
This work aims to study the airport sector and the Brazilian concession market and create a model for pricing the project from Guarulhos airport. Real data obtained from the concessionaire results and data made public, as inflation and GDP growth, as well as projections based on established premises are used. Different scenarios were considered in order to compare the results, which indicated a significant sensitivity of the model to passenger demand variations and also the flexibility of the investment schedule.